2019
DOI: 10.3390/jcm8050658
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sexual Function by Using Focal Vibrations in Men with Spinal Cord Injury: Encouraging Findings from a Feasibility Study

Abstract: Erectile dysfunction (ED) is a frequent and disabling condition in patients with spinal cord injury (SCI). Spasticity can negatively affect sexual intercourse, as it may interfere with positioning, mobility, and muscle activation and strength, leading to ED. The aim of our study was to evaluate the feasibility and efficacy of muscle vibration (MV) applied to the pelvic muscles in improving ED in men with SCI. Ten adult men with traumatic SCI were submitted to 15 sessions of MV, applied on the perineum and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Penile vibratory stimulation is the preferred treatment of men with anejaculation after SCI, and it is also effective in relieving spasm symptoms (86). Calabrò et al (87) recently reported the use of pelvic muscle vibration to treat ED of SCI patients. They performed muscle vibration treatment on 10 ED patients with incomplete SCI and found the amplitude of their pudendal nerve SEP was distinctly increased, and many patients reported an increase in sexual sensation in this study, although this increase was not statistically significant.…”
Section: Medication Surgery and Other Treatmentsmentioning
confidence: 99%
“…Penile vibratory stimulation is the preferred treatment of men with anejaculation after SCI, and it is also effective in relieving spasm symptoms (86). Calabrò et al (87) recently reported the use of pelvic muscle vibration to treat ED of SCI patients. They performed muscle vibration treatment on 10 ED patients with incomplete SCI and found the amplitude of their pudendal nerve SEP was distinctly increased, and many patients reported an increase in sexual sensation in this study, although this increase was not statistically significant.…”
Section: Medication Surgery and Other Treatmentsmentioning
confidence: 99%